Bowing Effect on Elastic Stability for Members Having Concave Configuration Shapes - Victor Yossif, Wisam (Journal of Engineering and Sustainable Development, 2007)
The Non-linear analysis of members having concave configuration shapes is considered using stability functions. The accuracy of results has been verified by using the finite element method by discretizing the beam-column member into different numbers of an equivalent prismatic element.The change of member lateral stiffness and change of member length are considered by using the stability and bowing functions after deriving them here.The axial deformation of concave beam-column including the effect of bowing is compared with the same of that without bowing effect to estimate the exact deformation of the beam-column under the same boundary condition and applied load.